2006
DOI: 10.1002/jlcr.1062
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [11C-carbonyl]hydroxyureas by a rhodium-mediated carbonylation reaction using [11C]carbon monoxide

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 19 publications
1
32
0
3
Order By: Relevance
“…Although it has been reported that heated zinc can reduce 11 C]CO 2 to 11 C]CO, this reaction did not work in our lab [36]. A possible explanation could be the use of 0.5% oxygen in the target gas, which is a factor 10 higher than used previously [24,36]. To circumvent potential deactivation of zinc by rapid oxidation, a column containing silica gel (100/120 mesh) was implemented to chromatographically purify 11 C]CO 2 .…”
Section: Resultsmentioning
confidence: 81%
“…Although it has been reported that heated zinc can reduce 11 C]CO 2 to 11 C]CO, this reaction did not work in our lab [36]. A possible explanation could be the use of 0.5% oxygen in the target gas, which is a factor 10 higher than used previously [24,36]. To circumvent potential deactivation of zinc by rapid oxidation, a column containing silica gel (100/120 mesh) was implemented to chromatographically purify 11 C]CO 2 .…”
Section: Resultsmentioning
confidence: 81%
“…[ (Fig. (47)), its structural analogue 1-hydroxy-3-phenyl[ 11 C]urea was synthesized using similar methods with 35±4% radiochemical yield decay-corrected (EOB) and a specific activity of 686 GBq/μmol [201]. This method provides a new way of synthesizing [ 11 C]hydroxyurea with more accurate chemical yield and greater radiochemical purity compared to earlier methods [202].…”
Section: Rhodium-mediated Carbonylationmentioning
confidence: 99%
“…[110] Abgelöst wurde dieses Verfahren durch die Einführung von Hochdruckreaktionssystemen (HPLC-Mikroautoklaven) [36,37] [117] oder 1,2,2,6,6-Pentamethylpiperidin [118] Rhodiumvermittelte Carbonylierungen [122][123][124] sind eine weitere Möglichkeit zur Einführung von [ 11 C]CO in organische Moleküle.…”
Section: Bei Den Stille-kreuzkupplungen Mit [unclassified
“…11 C-markierte Malonate, [123] Hydroxyharnstoffe, [122] Carbamate [124] und Diphenylharnstoffe [124] …”
Section: Bei Den Stille-kreuzkupplungen Mit [unclassified